АКТУАЛЬНІ ПРОБЛЕМИ БОРОТЬБИ З ДОМАШНІМ НАСИЛЬСТВОМ У СПОЛУЧЕНИХ ШТАТАХ АМЕРИКИ - Джужа, Анастасія Олександрівна (SUPREMANCE OF LAW, 2017)
It is clarified the main methods of detection and prevention of domestic violence based on the experience of the United States. The concept of domestic violence, its detection, behavior of a person who commits a crime was exposed and reviewed. Also it was analyzed the role of the victim and issues of domestic violence.
Keywords: domestic violence; identity of the offender; victim; violence in the family; physical violence; psychological impact